2016
DOI: 10.1038/aps.2016.14
|View full text |Cite
|
Sign up to set email alerts
|

Methylophiopogonanone A suppresses ischemia/reperfusion-induced myocardial apoptosis in mice via activating PI3K/Akt/eNOS signaling pathway

Abstract: Aim:The dried tuber root of Ophiopogon japonicus has been used in the traditional Chinese medicine for treatment of myocardial ischemia and thrombosis. In this study we investigated the effects of methylophiopogonanone A (MO-A), a major homoisoflavonoid in Ophiopogon japonicus, on myocardial ischemia/reperfusion (I/R) injury. Methods: Mice were pretreated with MO-A (10 mg· kg -1 ·d -1 , po) for 2 weeks and then subjected to transient occlusion of the left anterior descending coronary artery. Cardiac function w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 33 publications
(34 reference statements)
0
45
0
Order By: Relevance
“…The cell viability was assessed using the methylthiotetrazole (MTT) assay kit (Beyotime, China) according to the manufacturer’s protocol and previously reported protocol [17]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cell viability was assessed using the methylthiotetrazole (MTT) assay kit (Beyotime, China) according to the manufacturer’s protocol and previously reported protocol [17]. …”
Section: Methodsmentioning
confidence: 99%
“…Then, 20 µg of total protein was separated by 10% sodium dodecyl sulfate–polyacrylamide gel electrophoresis and transferred to nitrocellulose membranes (Millipore, MA, USA). The membranes were blocked for 30 min at 37°C with 5% nonfat dry milk and subsequently incubated with primary antibodies overnight at 4°C according to a previous protocol [17]. The primary antibodies against Notch-1, Notch-1 intracellular domain (Notch-1 ICD), Hes-1, cleaved caspase-3, caspase-3, and β-actin were purchased from Cell Signaling Technology (Shanghai, China).…”
Section: Methodsmentioning
confidence: 99%
“…PI3K/Akt is a transmembrane signal transduction cascade involved in the growth and apoptosis of myocardial cells, which also regulate coronary angiogenesis and downstream signal transduction . He et al demonstrated that activating the PI3K/Akt/eNOS signaling pathway attenuates myocardial apoptosis induced by ischemic‐reperfusion (I/R) in mice via cleaving caspase‐3 expression, elevating the Bcl‐2/Bax ratio, and restoring NO production.…”
Section: Introductionmentioning
confidence: 99%
“…It is involved in the regulation of important physiological functions such as cell activation, protein synthesis, and mediates numerous external stimulus signals to induce cell growth, differentiation, survival, apoptosis, and malignancy. Akt activates directly on multiple targets such as the apoptotic family of Bcl, nuclear transcription factor-κB (NF-κB) and nitric oxide synthase (NOS) and inhibits apoptosis by reducing open mPTP [30]. But, the mechanism of myocardial apoptosis is complex and involves multiple targets; whether EP reduces the myocardial apoptosis in exhausted Figure 6: e effect of EP on the levels of p-PI3K, p-Akt, Bad, Bax, Bcl-2, and caspase-3 proteins in the rat myocardium after EE (x ± s, n � 6).…”
Section: Discussionmentioning
confidence: 99%